Bash quick start guide : get up and running with shell scripting with Bash - Ryder, Tom (Packt Publishing, 2018)
Learn how to write shell script effectively with Bash, to quickly and easily write powerful scripts to manage processes, automate tasks, and to redirect and filter program input and output in useful and novel ways. Key Features Demystify the Bash command line Write shell scripts safely and effectively Speed up and automate your daily work Book Description Bash and shell script programming is central to using Linux, but it has many peculiar properties that are hard to understand and unfamiliar to many programmers, with a lot of misleading and even risky information online. Bash Quick Start Guide tackles these problems head on, and shows you the best practices of shell script programming. This book teaches effective shell script programming with Bash, and is ideal for people who may have used its command line but never really learned it in depth. This book will show you how even simple programming constructs in the shell can speed up and automate any kind of daily command-line work. For people who need to use the command line regularly in their daily work, this book provides practical advice for using the command-line shell beyond merely typing or copy-pasting commands into the shell. Readers will learn techniques suitable for automating processes and controlling processes, on both servers and workstations, whether for single command lines or long and complex scripts. The book even includes information on configuring your own shell environment to suit your workflow, and provides a running start for interpreting Bash scripts written by others. What you will learn Understand where the Bash shell fits in the system administration and programming worlds Use the interactive Bash command line effectively Get to grips with the structure of a Bash command line Master pattern-matching and transforming text with Bash Filter and redirect program input and output Write shell scripts safely and effectively Who this book is for People who use the command line on Unix and Linux servers already, but don't write primarily in Bash. This book is ideal for people who've been using a scripting language such as Python, JavaScript or PHP, and would like to understand and use Bash more effectively.